A case control study to evaluate correlation of anemia with severe preeclampsia - Gupta, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preeclampsia is a leading cause of maternal and perinatal morbidity and mortality worldwide. This study aims to evaluate correlation of anemia with severe preeclampsia. Methods: It is a prospective case control study conducted in Sultania Zanana Hospital, Bhopal over one year period. Patients were grouped as cases (severe preeclampsia with severe anemia, n=180) and controls (severe preeclampsia with no/mild/moderate anemia, n=180). Collecting data were compared using the Pearson chi square, fisher’s exact test and the independent t-test as appropriate. Logistic regression analysis was performed. Odds ratio (OR) and their corresponding 95% confidence intervals were calculated. Results: Higher incidence of maternal complications abruption (8.88% v/s 0.5%), ARF (2.2% v/s 0.5%), PPH (2.8%), pulmonary edema (5%), CCF (3.3%), HELLP (1.6%), CVA (1.1%), pulmonary embolism and DIC in 0.5% and maternal mortality seen in cases. Perinatal complications like pregnancy wastage (22.8% v/s 7.8%), IUGR (55.8% v/s 32%), early neonatal death (7.5% v/s 2.4%), NICU admission (31.3% v/s 20.7%) were more in cases. Conclusions: Perinatal and maternal complications are significantly associated with severity of anemia in preeclampsia women. Anemia being a easily detectable and modifiable risk factor, detection of anemia in early gestation can be a key to prevent or decrease the severity of preeclampsia.